Advertisement Remove all ads

Show that (A - B)(A + B) + (B - C) (B + C) + (C - A) (C + A) = 0 - Mathematics

Show that (a - b)(a + b) + (b - c) (b + c) + (c - a) (c + a) = 0

Advertisement Remove all ads

Solution

L.H.S = (a - b) (a + b) + (b - c) (b + c) + (c - a) (c + a)

= (a2 - b2) + (b2 - c2) + (c2 - a2) = 0 = R.H.S

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 8 Maths Textbook
Chapter 9 Algebraic Expressions and Identities
Exercise 9.5 | Q 5.5 | Page 151
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×